ANALYSIS OF THE TACTICAL BEHAVIOR OF YOUTH ACADEMY SOCCER PLAYERS - Henrique Bueno Américo; Felippe da Silva Leite Cardoso; Guilherme Figueiredo Machado; Marcelo Odilon Cabral de Andrade; Elton Ribeiro Resende; Israel Teoldo da Costa (Journal of Physical Education)
ABSTRACT The aim of this study was to compare the tactical behavior efficiency between soccer players from different age levels. The sample comprised 400 players from four age groups (Under-11, -13, -15, and -17), who performed 23,855 tactical actions. Players' tactical behavior efficiency was assessed through FUT-SAT. Statistical procedures included descriptive analysis and the tests Kolmogorov-Smirnov, Kruskal-Wallis and Mann-Whitney. The significance level adopted was p<0.05. Results indicated that the tactical behavior efficiency tends to increase over time, except for the U-15 age level, that displayed an accentuated drop in relation to the others. It is concluded that the efficiency of tactical behavior of the players in soccer displayed differences across different age levels.